Reconstructing Al-Māwardī’s Educational Thought: A Philosophical Analysis of ‘Adab al-Dunyā wa al-Dīn in Contemporary Islamic Education - Majid, Fahrudin; Tamam, Abas Mansur (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
This study aims to reconstruct Al-Māwardī’s educational theory as outlined in his work Adab Al Dunyā Wa Al Dīn to provide a comprehensive understanding of his contributions to Islamic education. By employing qualitative content analysis and focusing on the ontological, epistemological, and axiological dimensions of his thought, the research explores the relationship between religious principles and intellectual development in Al-Māwardī’s framework. This paper critiques existing literature on Al-Māwardī’s educational philosophy and addresses gaps in prior studies. The findings indicate that Al-Māwardī’s educational theory emphasizes the holistic development of individuals through the integration of knowledge and ethics, with the ultimate goal of achieving happiness in both the worldly and afterlife domains. The study highlights the relevance of his concepts—such as ta’dīb (moral education) and ta’līm (knowledge transmission)—to contemporary curriculum development and character education, proposing practical applications for modern Islamic educational contexts.